Euthanasia of dogs and cats by veterinarians in New Zealand: protocols, procedures and experiences. - Gates MC; Kells NJ; Kongara K; Littlewood KE (Taylor and Francis Group, 2023)
AIMS: To collect data on protocols used by New Zealand veterinarians to perform euthanasia of dogs and cats, and to explore opinions towards the training they received in euthanasia during veterinary school. METHODS: A cross-sectional survey was administered to all veterinarians registered with the Veterinary Council of New Zealand. The survey asked respondents about their practices' policies for euthanasia; protocols for performing euthanasia of dogs and cats; opinions towards euthanasia training received in veterinary school; and subsequent experiences with euthanasia in practice. Descriptive statistics were provided for all quantitative study variables and thematic analysis was performed on the free-text comments. RESULTS: The survey was completed by 361/1,448 (24.9%) veterinarians in companion or mixed animal practice. The mean numbers of dogs and cats euthanised each month were 7.2 (median 5; min 0; max 60) and 7.9 (median 5; min 0; max 60), respectively. Fewer than half of respondents reported that their clinic had a standard protocol for euthanising dogs (147/361; 40.7%) or cats (157/361; 43.5%). For euthanasia of dogs, 119/361 (32.9%) always used sedation while 71/361 (19.7%) indicated that they would not use sedation. For euthanasia of cats, 170/361 (47.1%) always used sedation while 53/361 (14.7%) indicated that they would not use sedation. Placement of IV catheters, methods for patient restraint, preferences towards the presence of owners during euthanasia, services provided with euthanasia, and discussions with owners were also highly variable and handled case-by-case depending on the client, patient, and clinical scenario. When asked about the euthanasia training received at veterinary school, it was generally ranked as below satisfactory, with approximately one-third of respondents indicating that they received no training in dealing with emotional clients (113/361; 31.3%), sedation protocols for euthanasia (107/361; 29.6%), or managing compassion fatigue (132/361; 36.6%). Most respondents (268/361; 74.2%) received no formal training in euthanasia after graduation and learned from experience or discussions with colleagues. Providing animals and owners with a good experience during the euthanasia process was highlighted as important for managing compassion fatigue. CONCLUSIONS: Euthanasia is a common procedure in companion animal practice and there is considerable variation in how veterinarians approach both the technical and non-technical elements. Training provided during veterinary school was generally considered below satisfactory, particularly regarding managing compassion fatigue and clients' emotional needs. CLINICAL RELEVANCE: Providing veterinarians with additional training on adapting their euthanasia protocols to different clinical scenarios may improve the experience for patients, owners and veterinary staff.
Keywords: Euthanasia; animal welfare; cat; cross-sectional survey; dog; education; Cats; Dogs; Animals; Humans; Veterinarians; Euthanasia, Animal; New Zealand; Cat Diseases; Cross-Sectional Studies; Compassion Fatigue; Dog Diseases; Surveys and Questionnaires